2014
DOI: 10.2478/amb-2014-0005
|View full text |Cite
|
Sign up to set email alerts
|

Early Clinical Effectiveness of ER:Yag Laser in Association with the Red Complex of Bacteria in the Initial Treatment of Moderate Chronic Periodontitis

Abstract: Summary Chronic periodontitis is a result of polymicrobial infection and its treatment aims removal of dental calculus and biofi lm from the periodontal pocket. Many hand and power-driven instruments are created for this purpose. In recent years, lasers are widely discussed tools for periodontal therapy. The aim of the present study is to evaluate the early microbiological and clinical effectiveness of the Er:YAG laser in the treatment of chronic periodontitis. 30 patients with moderate chronic periodontit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Since the Er:YAG laser is approved from FDA for bone surgery in 2004 it is used in various osseous procedures including crown lengthening (14). There are reports from the literature demonstrating lots of benefits of the laser like bactericidal effectiveness, less discomfort and vibrations to the patient, no tissue damage and healing complications, effectiveness in bone surgery (15,16). In the present study is noticed that the Er:YAG laser is effective not only in removing soft (excessive gingiva) and hard (bone) tissues, but it can be safe during the surgery without causing more bleeding or other side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Since the Er:YAG laser is approved from FDA for bone surgery in 2004 it is used in various osseous procedures including crown lengthening (14). There are reports from the literature demonstrating lots of benefits of the laser like bactericidal effectiveness, less discomfort and vibrations to the patient, no tissue damage and healing complications, effectiveness in bone surgery (15,16). In the present study is noticed that the Er:YAG laser is effective not only in removing soft (excessive gingiva) and hard (bone) tissues, but it can be safe during the surgery without causing more bleeding or other side effects.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 193 articles were possible to be included. Initial screening of the titles and abstract resulted in the further consideration of 179 publications to be excluded, and these 179 were excluded on the basis of studies that presented data on probing depth, clinical attachment level, and bleeding on probing (57); animal studies (44); studies that presented data on effect of erbium lasers on the root surface (33); literature reviews (31); and studies that presented data on calculus removal activity of the erbium lasers or conventional instruments (14), whereas the remaining (14) publications have been obtained and analyzed in full text.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, concluded that the microbiological analysis revealed that the pathogens from the red complex decreased 3 times in the control group (SRP) and 6 times in the test group (Er:YAG laser). Therefore, the Er:YAG laser demonstrates pronounced early effectiveness in chronic periodontitis treatment and would be an appropriate alternative to the conventional periodontal therapy; also, Er:YAG laser possesses a well-defined effectiveness in the treatment of moderate chronic periodontitis in the early healing period, which would be a prerequisite for long-term positive therapeutic outcomes [14].…”
Section: Antibacterial Effect Of the Conventional Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Last 20 years Er:YAG lasers are increasingly applied in periodontal procedure, since they can be applied for soft as well as for hard tissue treatment. Some of their properties and advantages include antibacterial action, predictable calculus removal, minimal root substance removal, and favor of cell attachment [5,6,7].…”
mentioning
confidence: 99%